PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DALAM MENINGKATKAN HASIL BELAJAR IPS PADA SISWA KELAS V SD INPRES PUNRANGA KECAMATAN PUJANANTING KABUPATEN BARRU - Abrina Maulidnawati Jumrah; Nur Afni (STKIP Andi Matappa Pangkep, 2019)
The purpose of this study was to find out how the application of Think Pair Share (TPS) Cooperative Learning Models and improvement of social studies learning outcomes through Think Pair Share (TPS) type Cooperative learning models for Grade V students of SD Inpres Punranga, Pujananting District, Barru Regency.The approach used in this research is descriptive qualitative approach. The type of research is classroom action research conducted based on the four stages of the research method from Arikunto (2010: 58), namely planning, implementation, observation, and reflection. The research subjects were 22 teachers and fifth grade students of SD Inpres Punranga. The instruments used in this study were observation sheets for teachers and students, learning achievement tests, and documentation. The data analysis technique obtained was analyzed qualitatively descriptive. the results of the study in cycle I reached 72% and in cycle 2 reached 100% showed that the application of the Think Pair Share (TPS) type of cooperative learning model can make a positive contribution in achieving student success and can improve student social studies learning outcomes, both individually and individually classical